Rock mass classification for rock slope stability assessment in Malaysia : a review - A. F., Salmanfarsi; H., Awang; Mohamad Idris, Ali (2019)
Rock mass classification systems are commonly used in the design and construction of rock engineering, and have seen widespread modifications and validations by various researchers over the last few decades. The rock mass classification, in particular the slope mass rating (SMR), continues to be the preferred preliminary method in small-scale assessment of rock slope stability. In Malaysia, parameters related to rock slope stability assessment have been modified to consider the condition of the rock mass such as the effect of heterogeneous rock units and weathering of rocks. The application of rock mass classifications however have been shown to contain some discrepancies, and the acknowledgement of the limitations of the system is important for an optimum use in the design stage. This paper reviews several development of rock mass classifications in Malaysia, as well as looking at potential direction of further development of the rock mass classification system in the context of local slope stability analysis.